Incidence, recurrence and management of electrical storm in Brugada syndrome - El-Battrawy, Ibrahim; Roterberg, Gretje; Kowitz, Jacqueline; Aweimer, Assem; Lang, Siegfried; Mügge, Andreas; Zhou, Xiaobo; Akin, Ibrahim (Frontiers in Cardiovascular Medicine, 2022)
Background Brugada syndrome (BrS) is associated with ventricular tachyarrhythmias. However, the presence of electrical strom (ES) and its management still debated. Objectives We present the outcome and management of 44 BrS patients suffering from ES. Methods A systematic literature review and pooled analysis Through database review including PubMed, Web of Science, Cochrane Libary and Cinahl studies were analyzed. Evidence from 7 reports of 808 BrS patients was identified. Results The mean age of patients suffering from ES was 34 ± 9.5 months (94.7% males, 65.8% spontaneous BrS type I). Using electrophysiological study ventricular tachycardia/ventricular fibrillation were inducible in 12/23 (52.2%). Recurrence of ES was documented in 6.1%. Death from ES was 8.2% after a follow-up of 83.5 ± 53.4. In up to 27 ES resolved without treatment. External shock was required in 35.6%, internal ICD shock in 13.3%, Overdrive pacing, left cardiac sympathetic block and atropin in 2.2%. Short-term antiarrhythmic management was as the following: Isopreterenol or Isopreterenol in combination with quinidine 35.5%, orciprenaline in 2.2%, quinidine 2.2%, disopyramide 2.2% or denopamide 2.2%. However, lidocaine, magensium sulfate, mexiletine and propanolol failed to control ES. Conclusion Although ES is rare in BrS, this entity challenges physicians. Despite its high mortality rate, spontaneous termination is possible. Short-term management using Isoproterenol and/or quinidine might be safe. Prospective studies on management of ES are warranted.